Involvement of the enteroendocrine system in intestinal obstruction. - Quentin Ballouhey; Laurence Richard; Laurent Fourcade; Ines Ben Rhaiem; Jean Michel Vallat; Franck Sturtz; Sylvie Bourthoumieu (PLoS ONE, 2017)
Intestinal atresia, a rare congenital condition, is often associated with intestinal motility disorders despite adequate neonatal surgery. Previous studies have focused on changes in the enteric nervous system (ENS). We hypothesized that other components of the digestive tract could be involved in this condition.In a rat model of surgically-induced intestinal obstruction, a transcriptome analysis was performed to measure the global gene expression. Then, analyzes were focused on genes expressed in ENS and neuroendocrine cells. Rat fetus small intestines at different developmental stages (ED15, ED17, ED19 and ED21, (n = 22)) were studied as controls and compared to the upper and lower segments of small intestines from rat fetuses with surgically-induced obstruction (n = 14; ligature at ED18). The gene expression pattern was confirmed by immunohistochemistry, electron microscopy and RT-qPCR.From ED15 to ED21, there was a physiological decrease in the gene expression of ENS markers and an increase in that of neuroendocrine genes. Regarding operated embryos, the changes in global gene expression were significantly higher in the proximal segment compared to the distal segment (18% vs. 9%). More precisely, a decrease in ENS gene expression and an increase in neuroendocrine gene expression were observed in the proximal segment compared to controls, indicating an accelerated maturation pattern. Immunohistochemistry and electron microscopy confirmed these findings.Fetal intestinal obstruction seems to induce an accelerated maturation in the proximal segment. Moreover, neuroendocrine cells undergo significant unexpected changes, suggesting that ENS changes could be associated with other changes to induce intestinal motility disorders.